Coenzyme Q0 Inhibits NLRP3 Inflammasome Activation through Mitophagy Induction in LPS/ATP-Stimulated Macrophages. (7th January 2022) - Hseu, You-Cheng; Tseng, Yu-Fang; Pandey, Sudhir; Shrestha, Sirjana; Lin, Kai-Yuan; Lin, Cheng-Wen; Lee, Chuan-Chen; Huang, Sheng-Teng; Yang, Hsin-Ling
Abstract : Coenzyme Q (CoQ) analogs with a variable number of isoprenoid units have exhibited as anti-inflammatory as well as antioxidant molecules. Using novel quinone derivative CoQ0 (2, 3-dimethoxy-5-methyl-1, 4-benzoquinone, zero side chain isoprenoid), we studied its molecular activities against LPS/ATP-induced inflammation and redox imbalance in murine RAW264.7 macrophages. CoQ0 's non- or subcytotoxic concentration suppressed the NLRP3 inflammasome and procaspase-1 activation, followed by downregulation of IL1 β expression in LPS/ATP-stimulated RAW264.7 macrophages. Similarly, treatment of CoQ0 led to LC3-I/II accumulation and p62/SQSTM1 activation. An increase in the Beclin-1/Bcl-2 ratio and a decrease in the expression of phosphorylated PI3K/AKT, p70 S6 kinase, and mTOR showed that autophagy was activated. Besides, CoQ0 increased Parkin protein to recruit damaged mitochondria and induced mitophagy in LPS/ATP-stimulated RAW264.7 macrophages. CoQ0 inhibited LPS/ATP-stimulated ROS generation in RAW264.7 macrophages. Notably, when LPS/ATP-stimulated RAW264.7 macrophages were treated with CoQ0, Mito-TEMPO (a mitochondrial ROS inhibitor), or N -acetylcysteine (NAC, a ROS inhibitor), there was a significant reduction of LPS/ATP-stimulated NLRP3 inflammasome activation and IL1 β expression. Interestingly, treatment with CoQ0 or Mito-TEMPO, but not NAC, significantly increased LPS/ATP-induced LC3-II accumulation indicating that mitophagy plays a key role in the regulation of CoQ0 -inhibited NLRP3 inflammasome activation. Nrf2 knockdown significantly decreased IL1 β expression in LPS/ATP-stimulated RAW264.7 macrophages suggesting that CoQ0 inhibited ROS-mediated NLRP3 inflammasome activation and IL1 β expression was suppressed due to the Nrf2 activation. Hence, this study showed that CoQ0 might be a promising candidate for the therapeutics of inflammatory disorders due to its effective anti-inflammatory as well as antioxidant properties.